Del Nido cardioplegia – what is the current evidence? - Sanetra, Krzysztof; Pawlak, Ireneusz; Cisowski, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2018)
Del Nido cardioplegia is believed to be both clinically and economically efficient. The interest in this myocardial protection method has been continuously growing. However, the evidence is not clear. The article summarizes recent reports regarding del Nido cardioplegia.